Extreme neonatal hyperbilirubinaemia in refugee and migrant populations: retrospective cohort - François Nosten; Rose McGready; Patrick Ferry van Rheenen; Claudia Turner; Eva Maria Nadine Wouda; Laurence Thielemans; Mue Chae Darakamon; Aye Aye Nge; Wah Say; Sanda Khing; Borimas Hanboonkunupakarn; Thatsanun Ngerseng; et al. (BMJ Publishing Group, 2020)
Objective To describe neonatal survival and long-term neurological outcome in neonatal hyperbilirubinaemia (NH) with extreme serum bilirubin (SBR) values.Design Retrospective chart review, a one-off neurodevelopmental evaluation.Setting Special care baby unit in a refugee camp and clinics for migrant populations at the Thailand-Myanmar border with phototherapy facilities but limited access to exchange transfusion (ET).Patients Neonates ≥28 weeks of gestational age with extreme SBR values and/or acute neurological symptoms, neurodevelopment evaluation conducted at 23-97 months of age.Main outcome measures Neonatal mortality rate, prevalence of acute bilirubin encephalopathy (ABE) signs, prevalence of delayed development scores based on the Griffiths Mental Development Scale (GMDS).Results From 2009 to 2014, 1946 neonates were diagnosed with jaundice; 129 (6.6%) had extreme SBR values during NH (extreme NH). In this group, the median peak SBR was 430 (IQR 371-487) µmol/L and the prevalence of ABE was 28.2%. Extreme NH-related mortality was 10.9% (14/129). Median percentile GMDS general score of 37 survivors of extreme NH was poor: 11 (2-42). 'Performance', 'practical reasoning' and 'hearing and language' domains were most affected. Four (10.8%) extreme NH survivors had normal development scores (≥50th centile). Two (5.4%) developed the most severe form of kernicterus spectrum disorders.Conclusion In this limited-resource setting, poor neonatal survival and neurodevelopmental outcomes, after extreme NH, were high. Early identification and adequate treatment of NH where ET is not readily available are key to minimising the risk of extreme SBR values or neurological symptoms.